Occlusal Pressure Redistribution with Single Implant Restorations. Issue 4 (5th October 2016) - Roque, Miguel A.; Gallucci, German O.; Lee, Sang J.
Abstract: Purpose: To describe the occlusal pressure redistribution in dental arches following placement of single posterior implant‐supported restorations in occlusion with natural dentitions. Materials and Methods: Fifteen patients who presented for successfully osseointegrated single posterior implant restorations participated in the study. Cement‐retained, all‐ceramic implant crowns were fabricated and delivered after adjustment for interproximal contacts, fit, and uniform occlusal contacts. Occlusal pressure distribution was recorded with a digital sensor that reported contact point forces as a percentage of total pressure applied to the sensor. Measurements were taken before and after restoration for comparison. The distribution of relative occlusal stress was analyzed for statistical significance by location. Results: The results indicated that placement of posterior implant‐supported restorations increased the bite pressure in the sextants containing the restorations by an average of 4.18% ( p = 0.019) of the maximum value registered (maximum bite pressure). The contralateral occlusal load was found to decrease by 2.9% ( p = 0.047) of the maximum value registered; however, there was no significant difference among or between the tooth positions. Conclusion: Single posterior implant‐supported restorations significantly increased the percentage (%) of total occlusal pressure in the containing sextant and decreased percentage of total occlusal pressure in the contralateral sextant. When analyzing restorations by exact position, more posterior implant restorations decreased the occlusal pressure applied in anterior dentitions.